Caribbean Maritime Security - Morris, Michael A. author. aut Link
IX, 231 p.
Keywords: Caribbean coast guard and naval hierarchies are developed in order to facilitate systematic comparisons about maritime issues and key actors. On this basis, the relationship of different groups of states to the longstanding Cold-War security agenda as well as the emerging post-Cold War one is assessed. Prominent emerging security issues include boat people, maritime drug trafficking and a variety of local maritime security issues. While Caribbean maritime security is distinctive and important, this book provides the only comprehensive treatment of the subject.